AUTOMATIC SOLAR TRACKING SYSTEM (Journal of Pharmaceutical Negative Results, 2023)
Solar energy, amongst a variety of sustainable energy sources, is the main energy and has quickly acquired its importance. A sun-based global positioning framework can provide generous levels of energy that make the utility of solar chargers much more efficient. The inverse proportionality of solar rays and solar-powered chargers is an explanation for their efficiency: financially, the initial cost and development components of a model for a sun-oriented global positioning framework with a sole opportunity center. The basic control circuitry relies on the NodeMcu microcontroller. The gadget is programmed such that the LDR sensor guides the DC motor in the direction the solar charger should turn, depending on the sun's rays. This positions the solar charger to capture the maximum amount of sunlight. In relation to other motors, DC motors are the simplest and smoothest motors, with high power and moderately slow speed. All exceptions can be accounted for and programmed to adjust course. 1985 saw the first production of solar-based silicon cells with 20% efficiency. But while improving the efficiency of solar chargers had compelling benefits, error-free was a great goal. Below 40% most boards float to work. To meet individual needs or buy own frameworks with appropriate results group of people need to buy different boards.